2003
DOI: 10.1083/jcb.200307111
|View full text |Cite
|
Sign up to set email alerts
|

A core function for p120-catenin in cadherin turnover

Abstract: p120-catenin stabilizes epithelial cadherin (E-cadherin) in SW48 cells, but the mechanism has not been established. Here, we show that p120 acts at the cell surface to control cadherin turnover, thereby regulating cadherin levels. p120 knockdown by siRNA expression resulted in dose-dependent elimination of epithelial, placental, neuronal, and vascular endothelial cadherins, and complete loss of cell–cell adhesion. ARVCF and δ-catenin were functionally redundant, suggesting that proper cadherin-dependent adhesi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

45
697
4
10

Year Published

2005
2005
2018
2018

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 663 publications
(756 citation statements)
references
References 45 publications
45
697
4
10
Order By: Relevance
“…29,30,33 Therefore, we investigated whether loss of p120 association with mutant E-cadherin lead to increased interaction with Hakai. Although the expression levels of Hakai remain unchanged (Figure 3c), we verified that E-cadherin mutations that block p120 association, those located at p120 binding domain, resulted in a significant increase of the interplay with Hakai: 1.84-fold for R749W (P ¼ 0.027), 2.29-fold for E757K and 1.73-fold for E781D (P ¼ 0.036) (Figures 3a and b).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…29,30,33 Therefore, we investigated whether loss of p120 association with mutant E-cadherin lead to increased interaction with Hakai. Although the expression levels of Hakai remain unchanged (Figure 3c), we verified that E-cadherin mutations that block p120 association, those located at p120 binding domain, resulted in a significant increase of the interplay with Hakai: 1.84-fold for R749W (P ¼ 0.027), 2.29-fold for E757K and 1.73-fold for E781D (P ¼ 0.036) (Figures 3a and b).…”
Section: Resultsmentioning
confidence: 99%
“…23 The p120-catenin is the best known inhibitor of cadherin endocytosis, as its binding to the E-cadherin juxtamembrane domain is required for maintenance and stability of E-cadherin molecules at the PM and, simultaneously, it physically blocks the interaction with proteins from the endocytic machinery, such as clathrin adaptor proteins and Hakai. [29][30][31][32][33] Importantly, Hakai binds directly to E-cadherin and, being an E3 ubiquitin ligase, it ubiquitinates and induces E-cadherin endocytosis. 33 Taking into account the present knowledge about E-cadherin regulation, we tested whether and how the E-cadherin cytoplasmic mutations interfere with key trafficking-related partners, leading to abnormal E-cadherin expression, localization and function, supporting their pathogenic relevance.…”
Section: Cdh1 Missense Mutations Affect E-cadherin Subcellular Localimentioning
confidence: 99%
See 1 more Smart Citation
“…If p120 at the cell-surface regulates cadherin levels by controlling cadherin turnover [7], we could expect that modifications to p120 such as serine/threonine phosphorylation might influence cadherin stability at the cell-surface. Since increased E-cadherin trafficking occurs in response to weakening or disrupting cell-cell adhesion [44], we treated S2-013 3A and S2-013 4A cells with EGTA and found that E-cadherin underwent faster degradation in S2-013 4A cells than in S2-013 3A cells (not shown).…”
Section: A Role For P120 Regulatory Domain In Stabilizing E-cadherinmentioning
confidence: 99%
“…p120 has multiple biological functions including regulation of cell adhesion by controlling cadherin turnover at the cell surface [7]. Cells expressing Ecadherin with a defective p120 binding site (764EED/AAA) failed to recruit p120 into the cadherin-catenin complex, and have reduced cell-cell adhesion, highlighting the importance of p120 in cadherin function [8].…”
Section: Introductionmentioning
confidence: 99%